From the Lab to the Farm: An Industrial Perspective of Plant Beneficial Microorganisms - Parnell, J. Jacob; Berka, Randy; Young, Hugh A.; Sturino, Joseph M.; Kang, Yaowei; Barnhart, D. M.; DiLeo, Matthew V. (Frontiers in Plant Science, 2016)
Any successful strategy aimed at enhancing crop productivity with microbial products ultimately relies on the ability to scale at regional to global levels. Microorganisms that show promise in the lab may lack key characteristics for widespread adoption in sustainable and productive agricultural systems. This paper provides an overview of critical considerations involved with taking a strain from discovery to the farmer’s field. This paper will review some of the most effective microbial products on the market today, explore the reasons for their success and outline some of the major challenges involved in industrial production and commercialization of beneficial strains for widespread agricultural application. General processes associated with commercializing viable microbial products are discussed in two broad categories, biofertility inoculants and biocontrol products. Specifically, we will address what farmers desire in potential microbial products, how mode of action informs decisions on product applications, variation in laboratory and field study data, challenges with scaling for mass production, and the importance of consistent efficacy, product stability and quality. In order to make a significant impact on global sustainable agriculture, the implementation of plant beneficial microorganisms will require a more seamless transition between laboratory and farm application. Early attention to the challenges presented here will improve the likelihood of developing effective microbial products that will improve crop yields, decrease disease severity, and help to feed an increasingly hungry planet.